A comparative analysis of the binary and multiclass classified chest X-ray images of pneumonia and COVID-19 with ML and DL models - Pal Madhumita; Mohapatra Ranjan K.; Sarangi Ashish K.; Sahu Alok Ranjan; Mishra Snehasish; Patel Alok; Bhoi Sushil Kumar; Elnaggar Ashraf Y.; El Azab Islam H.; Alissa Mohammed; El-Bahy Salah M. (Open Medicine)
The highly infectious coronavirus disease 2019 (COVID-19) is caused by severe acute respiratory syndrome coronavirus 2, the seventh coronavirus. It is the longest pandemic in recorded history worldwide. Many countries are still reporting COVID-19 cases even in the fifth year of its emergence.